Evaluation of Adherence to World Health Organization Guidelines on Clinical Management of Cryptococcal Meningitis among Health Care Providers in Selected Hospitals, Kisumu, Kenya - Ogendo, Robina (Global Journal of Health Sciences, 2025)
Purpose: Prevalence of Cryptococcal meningitis has risen and remained high over the last several decades in line with the HIV/ADS pandemic which has consequently led to the increase of Cryptococcal Meningitis associated mortality rates ranging from 17% to 100% in Africa. The aim of the present study was to assess the adherence to WHO guidelines on clinical management of CM in adults among HCP in JOOTRH and KCRH. Methodology: This was a cross-sectional analytical study which was carried out in Kisumu County, Kenya. Sample size was obtained using Yamane (1967) formula. The sample calculation yielded a sample size of 119 respondents with a 97% response rate. Bivariate analysis was done using logistic regression from which chi square, odds ratios and the p- values were drawn Findings: Findings from demographics showed that many were females (n=64, 55.2 %). Distribution of age bracket showed that many (n=74, 64.3%) were aged 30 years or below. From the results,76%(n=88) reported using lumbar puncture with rapid CrAg assay while very few reported using lumbar puncture with rapid cerebral spinal fluid India ink test (3%, n=4) in diagnosing cryptococcal meningitis. Majority (90.5%, n=105) reported using amphotericin B deoxycholate + fluconazole as first line antifungal therapy. In management of hypokalemia, majority (93%, n=56) did not monitor potassium daily but all (100%, n=60) administered 1 liter of normal saline infused with 20 mEq of potassium chloride two hours prior to each infusion of amphotericin B. 93%(n=56) did not administer two of 250-mg tablets of magnesium trisilicate, or magnesium chloride 4 mEq twice/ day for supplementation of magnesium. Unique Contribution to Theory, Practice and Policy: This study recommends that the County government of Kisumu in collaboration with the two hospital management teams, need to organize and provide periodic training opportunities for the health care providers on the WHO guidelines on management of Cryptococcal meningitis whose prevalence is high in this region, and consistently avail current recommended clinical guideline/protocols in all the clinical departments to ease reference, hence promote adherence. In addition, they should include the aspect of adherence to WHO guidelines on management of cryptococcal meningitis, as one of the yearly appraisal objectives and provide timely supportive supervision in order to promote and streamline optimal adherence.